Nudity, feminists, and Chinese online censorship: A case study on the anti-domestic violence campaign on SinaWeibo. (November 2019) - Han, Ling; Lee, Chengpang
Chinese feminist activists are actively participating in the Chinese online public sphere. In this study, we examine a case – the Anti-Domestic Violence with Nude Photos Campaign (裸照反家暴活动) – and the response of Chinese online censorship to this campaign. Campaign activists used nude photos to mobilize the public's support. According to the existing theoretical perspectives such as the collective action potential theory, this kind of online campaign with pornographic elements and the potential to mobilize people is very likely to be censored. Counter to this expectation, we found that not all of the original photos were removed. Our finding suggests that the interactive manner in which activists responded to the public on SinaWeibo's discussion threads matters in terms of the degree of censorship. This study complements the existing studies on the Chinese online censorship system, echoes scholars' call for studies on censorship from a more interactive angle, and furthers our understanding of the Chinese feminist movement.